Estudio farmacognóstico de Werneria Apiculata y Werneria Marcida S.F. Blake - Zárate, Rosa (1999)
Of the species Werneria apiculata and Werneria marcida S. F. Blake of the Asteracae family it can be extracted and identified: reducing sugars (glucose, levulose) guns, tannins, steroids, fenolic compunds, flanvonoids, alcaloids. lt has been found in W. Marcida low concentration of the same principies.The biological assays of the Artemia Salina Leach, both species present biodinamic activity. W apiculata presents greater bronco-dilatador activity and antiinflamatory than W Marcida.The terapeutic activity of these species is due the presence of flavonoids, that were obteined as the mayor constituyents that we think participate in a pronounded way in the total activity of the drug.